2016
DOI: 10.18632/oncotarget.11315
|View full text |Cite
|
Sign up to set email alerts
|

Boar seminal plasma exosomes maintain sperm function by infiltrating into the sperm membrane

Abstract: Seminal plasma ingredients are important for maintenance of sperm viability. This study focuses on the effect of boar seminal plasma exosomes on sperm function during long-term liquid storage. Boar seminal plasma exosomes had typical nano-structure morphology as measured by scanning electron microscopy (SEM) and molecular markers such as AWN, CD9 and CD63 by western blot analysis. The effect on sperm parameters of adding different ratio of boar seminal plasma exosomes to boar sperm preparations was analyzed. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(103 citation statements)
references
References 50 publications
2
93
0
6
Order By: Relevance
“…Of particular interest was the up-regulation of HSD17B8 in the UTJ, suggesting that the SP may play a role in sperm attachment and release from the oviduct reservoir via estrogen signaling regulation. It is known that exosomes present in SP bind to the sperm head membrane and improve membrane integrity 74 . Also, it has been stated that proteins present in SP are involved in the immune and inflammatory response in the uterus 75 .…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest was the up-regulation of HSD17B8 in the UTJ, suggesting that the SP may play a role in sperm attachment and release from the oviduct reservoir via estrogen signaling regulation. It is known that exosomes present in SP bind to the sperm head membrane and improve membrane integrity 74 . Also, it has been stated that proteins present in SP are involved in the immune and inflammatory response in the uterus 75 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a llama seminal lectin (SL15) that is likely adsorbed to spermatozoa via SP during ejaculation and is probably involved in sperm reservoir formation (Zampini, Sequeria, Argañaraz, & Apichela, ). In other species, some components of SP have been shown to act as protective agents against premature capacitation, which would seem to indicate the need to add a certain percentage of SP to cryopreservation diluents (Du et al, ; Kershaw‐Young & Maxwell, ). All the above denotes the important role of SP in reproductive physiology.…”
Section: Introductionmentioning
confidence: 99%
“…Aalberts et al [ 249 ] found the tetraspanin CD9 in human prostasomes and later CD9, specifically associated with 50–150 nm vesicles [ 250 ]. Du et al [ 251 ] observed a positive effect of CD9- and CD63-positive EVs (exosomes) isolated from boar seminal plasma on several parameters of sperm ‘quality’. Sperm showed prolonged effective motility time, improved plasma membrane integrity and antioxidant capacity, and inhibited premature capacitation.…”
Section: Tetraspanins In Evs Of the Female And Male Reproductive Smentioning
confidence: 99%